KAJIAN REGULASI PEMBENTUKAN BANK TANAH - Artati, Sri Untari Indah (Ensiklopedia of Journal, 2024)
The Land Bank is a special agency (sui generis), an Indonesian legal entity established by the central government and given special authority to oversee land (Article 1 of Law No. 64 of 2021). The concept of a land bank is basically to collect land, especially abandoned land and land directly controlled by the state that has not been utilized, then develop, collect, and give back in accordance with the land use plan. Land Banking also serves as a tool to manage land utilization and use to increase land productivity. By the Government it is intended for long-term use and implements a public land policy. The problems are 1) How is the regulation and concept of Land Bank establishment in Indonesia and 2) How is the use of land that has been collected by the land bank. By using normative research methods, the author aims to discuss these issues. This study concludes that as stated in the mandate of the Preamble and Article 33 of the 1945 Constitution, the establishment of a land bank is the responsibility of the state to create welfare and prosperity for all Indonesian people, and the collected land is used for fundamental purposes for the community and public interest. The author's suggestion is that a detailed regulation be made on the use of land from the land bank and emphasize on several fundamental interests.  Keywords: Land Bank; Regulation; Land Use